PERSEPSI SISWA SMU UPH COLLEGE TERHADAP KETERAMPILAN LITERASI INFORMASI DALAM PENULISAN [UPH COLLEGE STUDENTS’ PERCEPTIONS OF INFORMATION LITERACY SKILLS IN WRITING] - Dhama Gustiar Baskoro (Polyglot, 2018)
This article has been retracted by the publisher because the author informed the editor that he has committed an act of research misconduct producing the article that violated publication ethics.